Problematik Pengaturan Pembatalan Peraturan Desa - Fathorrahman Fathorrahman (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Village Regulations according to Article 8 of the PPP Law are considered part of statutory regulations. This is in line with the previous PPP Law which placed Perdes as part of the Regional Regulations. With the recognition that Perdes are part of the national legal regulation system, the reversal also follows the regime of annulment of legislation. In the existing retaliation regime, it must go through judicial instruments, namely through the MK and MA. Particularly for village regulations, because their position is under the law, they go through the MA institution. However, the mechanism is regulated differently in the Village Law. The method used is the juridical-normative research model. From this research, there are several illustrations that the model for canceling Perdes regulated in the Village Law is a problem. Both from the aspect of the regulatory model and from the theoretical aspect.